The impact of the expressionist movement on contemporary Iraqi plastic art (Journal of the College of Basic Education, 2023)
The ancient man was able to express his innate motives and desires with drawings in which he wrote his first pictorial epics on the ceilings and walls of the caves, which indicated efficiency, expressive vitality, and realistic accuracy. controlling his prey. In the era of stability, agriculture, and the emergence of human groups in the Neolithic era, man expressed additional desires and different motives that represented rain and the glorification of fertility and reproduction, so he expressed their achievement in drawings and dolls representing the mother gods, then his expression changed towards nature to express his mythological and religious vision of a religious thought of the plurality of gods. On the land of Sumer, the power of expression increased, as he expressed his civilized reality and the maturity of his religious and life rituals with artistic methods based on distortion, the strength of lines, and exaggeration with many techniques between notching, digging, rubbing, and inlaying with natural stones. The expression was clear and obvious in the eyes of the worshipers and the stagnation of their devotional movements in the simplicity of the composition and the reduction of the forms. A person expresses when he finds an outlet for expression through the arts, i.e. the expression of a person's emotional, intellectual and practical activity. It expresses the conscience of its society, and according to what Young says about the (collective unconscious): Expression is an activity and a creative activity as well, and it is not only a surrender to motives and incentives, but rather it is a creative, aesthetic, expressive process. In ancient Egypt, man expressed his religious vision of his immortality in another world by building pyramids, and in the era of the Middle Kingdom - the era of Akhenaten - the expressionist current flourished after the departure of the official stereotyped style, so the king was drawn with his bliss in line and distortion in shape. And after the crystallization of the analytical human mentality, where the logic and philosophical thought of the Greeks continued, the expression of ideals and the glorification of the ideal beauty in the human, harmonious, athletic (Olympic) body continued. He resorted to expression based on exaggeration, distortion and distortion of proportions.